Design, implementation and long-term follow-up of a context specific trauma training course in Uganda: Lessons learned and future directions - Ullrich, Sarah J.; Kilyewala, Cathy; Lipnick, Michael S.; Cheung, Maija; Namugga, Martha; Muwanguzi, Peter; DeWane, Michael P.; Muzira, Arlene; Tumukunde, Janat; Kabagambe, Monica; Kebba, Naomi; Galukande, Moses; et al. (The American Journal of Surgery, 2020)
The Kampala Advanced Trauma Course (KATC) was developed in 2007 due to a locally identified need for an advanced trauma training curriculum for the resource-constrained setting. We describe the design, implementation and evaluation of the course.The course has been delivered to over 1,000 interns rotating through surgery at Mulago National Referral Hospital. Participants from 2013 to 2016 were surveyed after completion of the course.The KATC was developed with local faculty and includes didactic and simulation modules. Over 50% of survey respondents reported feeling confident performing and teaching 7 of 11 course skills and felt the most relevant skill was airway management(30.2%). Participants felt least confident managing head trauma(26.4%). Lack of equipment(52.8%) was identified as the most common barrier to providing trauma care.Providers are confident with most skill sets after taking the KATC. Minimal dependence on instructors from high-income countries has kept the course sustainable and maximized local relevance.
Keywords: Trauma course; ATLS; Africa; Uganda; Surgical education; Training